2014
DOI: 10.1016/j.psyneuen.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective lentiviral-mediated suppression of microRNA124a in the hippocampus evokes antidepressants-like effects in rats

Abstract: Summary Several lines of evidences suggest that the brain-derived neutrophic factor (BDNF) is implicated in the pathophysiology of depression. However, the molecular mechanisms are not fully understood. In the current study we aimed to investigate how genetic modulation of BDNF in the hippocampus using microRNa124a (miR124a)-expressing lentiviral vectors (LV) might affect depression-like behavior in adult rats. For this purpose, we assessed the expression level of miR124a and its direct target BDNF in the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 48 publications
3
57
1
Order By: Relevance
“…In contrast, another study by Bahi et al [16] reported that virus-mediated miR-124 overexpression exacerbated, whereas inhibition decreased, stress-induced depressionlike behavior in rodents [16]. The differences in these two findings are not clearly known; however, model species, genetic Figure 1.…”
Section: Potential Role Of Mir-124 In Neuronal Differentiation Stresmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, another study by Bahi et al [16] reported that virus-mediated miR-124 overexpression exacerbated, whereas inhibition decreased, stress-induced depressionlike behavior in rodents [16]. The differences in these two findings are not clearly known; however, model species, genetic Figure 1.…”
Section: Potential Role Of Mir-124 In Neuronal Differentiation Stresmentioning
confidence: 95%
“…Whereas in Higuchi study [15], AAV vectors were used with the Camk2a promoter to overexpress miR-124 specifically in excitatory neurons, Bahi et al [16] used lentiviral vector where expression was driven by cytomegalovirus promoter. This suggests that the role of miR-124 in stress/depression may be cell type specific.…”
Section: Potential Role Of Mir-124 In Neuronal Differentiation Stresmentioning
confidence: 99%
“…Some studies have also shown that miRNAs can induce depressive-like phenotype. Recently, Bahi et al 2014 found that hippocampal miR-124a overexpression can contribute to social stress-induced depression through suppressing BDNF expression. The study also showed that miR-124a was up-regulated in the hippocampus but not in the cortex and BDNF transcripts were down regulated.…”
Section: Animal Models Of Depressionmentioning
confidence: 99%
“…Moreover, inhibition of BDNF-AS by administrating a sequence-specific inhibitor called an antagoNAT or knockdown of BDNF-AS by siRNA both induce up-regulation of BDNF mRNA and protein expression in vitro and in vivo, leading to increased glial-derived neurotrophic factor (GDNF) and ephrin receptor B2 (EPHB2) mRNA as well as enhanced neurite outgrowth and maturation (Modarresi et al, 2012). Additionally, in the 3ʹ untranslated region (3ʹUTR) of BDNF appears a sequence complementarity of this noncoding transcript, meanwhile there also contains regulatory miRNA-binding sites such as miR-124a (Bahi et al, 2014). Intriguingly, miR-124 is demonstrated to modulate depression and related neurobehavioral deficits, therefore BDNF-AS may partly function to inhibit miR-124 binding to BDNF (Kocerha et al, 2015), suggesting an important role of BDNF-AS in MDD (Fig.…”
Section: Lncrnas Related To Synaptic Plasticity Potentially Associatementioning
confidence: 99%